2022
DOI: 10.1007/s12011-022-03363-8
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Metabolism and Thyroid Function During the Perinatal Period: Maternal-Neonatal Correlation and Effects of Topical Povidone-Iodine Skin Disinfectants

Abstract: An adequate maternal iodine intake during pregnancy and lactation is essential for growth and mental development in fetuses and newborns. Both de cient and excess iodine may disrupt normal thyroid function. There are limited data on perinatal iodine metabolism in mothers and infants, as well as the effect of povidone-iodine (PVP-I) antiseptics used in Cesarean delivery. The urinary iodine concentration (UIC), serum iodine, thyrotropin (TSH), free thyroxine (FT4) and breast milk iodine concentration (BMIC) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…These factors include the use of iodine antiseptics during delivery, preterm birth, low BW, male sex, and days of life at the time of sample collection. 11,20,21 This study found a higher prevalence of nTSH levels ≥ 5 mIU/L among term newborns than preterm newborns. These findings are consistent with research describing a higher incidence of thyroid dysfunction among preterm newborn infants, especially extremely preterm infants, due to the immaturity of the hypothalamic-pituitary- thyroid axis.…”
Section: Discussionmentioning
confidence: 53%
“…These factors include the use of iodine antiseptics during delivery, preterm birth, low BW, male sex, and days of life at the time of sample collection. 11,20,21 This study found a higher prevalence of nTSH levels ≥ 5 mIU/L among term newborns than preterm newborns. These findings are consistent with research describing a higher incidence of thyroid dysfunction among preterm newborn infants, especially extremely preterm infants, due to the immaturity of the hypothalamic-pituitary- thyroid axis.…”
Section: Discussionmentioning
confidence: 53%
“…Entre estos factores, se incluyen el uso de antisépticos yodados durante el parto, los nacimientos prematuros, el bajo PN, el sexo masculino y los días de vida al momento de la toma de la muestra. 11,20,21 En este estudio, se observó una mayor prevalencia de TSHn ≥5 mUI/l en nacidos a término en comparación con prematuros. Estos hallazgos coinciden con investigaciones que describen una mayor incidencia de disfunción tiroidea en los prematuros, especialmente en los extremos, debido a la inmadurez del eje hipotálamo-hipófiso-tiroideo.…”
Section: Discussionunclassified
“…Therefore, to reduce the risk of neonatal hypothyroidism, healthcare and dental hygiene professionals should carefully consider the advantages and dangers and use caution when prescribing or suggesting povidone-iodine or any antiseptic agent to pregnant persons. (33) 8.…”
Section: Safety and Side Effectsmentioning
confidence: 99%